Origin and evolution of metal P-type ATPases in Plantae (Archaeplastida) - Hanikenne, Marc; Baurain, Denis (Frontiers in Plant Science, 2014)
Metal ATPases are a subfamily of P-type ATPases involved in the transport of metal cations across biological membranes. They all share an architecture featuring eight transmembrane domains in pairs of two and are found in prokaryotes as well as in a variety of Eukaryotes. In Arabidopsis thaliana, eight metal P-type ATPases have been described, four being specific to copper transport and four displaying a broader metal specificity, including zinc, cadmium and possibly copper and calcium. So far, few efforts have been devoted to elucidating the origin and evolution of these proteins in Eukaryotes. In this work, we use large-scale phylogenetics to show that metal P-type ATPases form a homogenous group among P-type ATPases and that their specialisation into either monovalent (Cu) or divalent (Zn, Cd…) metal transport stems from a gene duplication that took place early in the evolution of Life. Then, we demonstrate that the four subgroups of plant metal ATPases all have a different evolutionary origin and a specific taxonomic distribution, only one tracing back to the cyanobacterial progenitor of the chloroplast. Finally, we examine the subsequent evolution of these proteins in green plants and conclude that the genes thoroughly characterised in model organisms are often the result of lineage-specific gene duplications, which calls for caution when attempting to infer function from sequence similarity alone in non-model organisms.